1992
DOI: 10.1002/pro.5560010113
|View full text |Cite
|
Sign up to set email alerts
|

Gln‐41 is intermolecularly cross‐linked to Lys‐113 in F‐actin by N‐(4‐azidobenzoyl)‐putrescine

Abstract: The bifunctional reagent N-(4-azidobenzoyl)-putrescine was synthesized and covalently bound to rabbit skeletal muscle actin. The incorporation was mediated by guinea pig liver transglutaminase under conditions similar to those described by Takashi (1988, Biochemistry 27, 938-943); up to 0.5 M/M were incorporated into G-actin, whereas F-actin was refractory to incorporation. Peptide fractionation showed that at least 90% of the label was bound to Gln-41. The labeled G-actin was polymerized, and irradiation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…This model agrees well with the structural model derived from other data fitting techniques (6,7) and optical reconstruction of electron micrographs of actin filaments (8 -10). The orientation of the monomer in the helix in this model agrees with the results of a genetic study of the F-actin binding site of phalloidin (11), chemical cross-linking experiments (12), and antibody decoration experiments (13,14). However, there is little evidence concerning the validity of the model pertaining to the intermonomer contacts that stabilize the helix.…”
supporting
confidence: 73%
“…This model agrees well with the structural model derived from other data fitting techniques (6,7) and optical reconstruction of electron micrographs of actin filaments (8 -10). The orientation of the monomer in the helix in this model agrees with the results of a genetic study of the F-actin binding site of phalloidin (11), chemical cross-linking experiments (12), and antibody decoration experiments (13,14). However, there is little evidence concerning the validity of the model pertaining to the intermonomer contacts that stabilize the helix.…”
supporting
confidence: 73%
“…The hydrophobic plug at the tip of the loop can now insert into a hydrophobic pocket formed by the interface of two monomers on the opposing strand of the helix, leading to an appreciable increase in the cross-strand stabilization available for the actin filament. Good agreement exists between this model and the results of low resolution structural studies (8 -10), protein chemical studies (11), and antibody decoration studies (12)(13). However, the model remains in large part unproven.…”
mentioning
confidence: 53%
“…The lack of DALP labeling of other abundant proteins of the cellular machinery (such as tubulin) also points to the specificity of actin labeling. It was also demonstrated that Gln-41 is the main amine acceptor site for the transglutaminase reaction (39,40), and the enzyme can also form trace amounts of covalently cross-linked actin oligomers from G actin, which may act as "seeds" to allow actin to polymerize faster. Furthermore, since Gln-41 is accessible in F actin as well (39) and according to our present results the high molecular weight polymers formed by TGase are also labeled by DALP, it is very likely that additional proteins are attached covalently, through their accessible Lys residues, to the microfibrillar meshwork by the enzyme.…”
Section: Discussionmentioning
confidence: 99%